Congestive Heart Failure: Experimental Model - Corno, Antonio F.; Cai, Xue; Jones, Caroline B.; Mondani, Giuseppina; Boyett, Mark R.; Jarvis, Jonathan C.; Hart, George (Frontiers in Pediatrics, 2013)
INTRODUCTION. Surgically induced, combined volume and pressure overload has been used in rabbits to create a simplified and reproducible model of acute left ventricular (LV) failure. MATERIALS AND METHODS. New Zealand white male rabbits (n=24, mean weight 3.1±0.2kg) were randomly assigned to either the Control group (n=10) or to the Heart Failure group (HF, n=14). Animals in the Control group underwent “sham” procedures. Animals in the HF group underwent procedures to induce LV volume overload by inducing severe aortic valve regurgitation with aortic cusp disruption and pressure overload using an occlusive silver clip positioned around the pre-renal abdominal aorta. RESULTS. Following Procedure-1 (volume overload) echocardiography confirmed severe aortic regurgitation in all animals in the HF group, with increased mean pulse pressure difference from 18±3mmHg to 38±3mmHg (P